Penyuluhan Edukasi Kesetaraan Gender untuk Kesehatan Mental bagi Ibu Rumah Tangga di Desa Tangga Batu - Putri, Annie Mustika; Marsya, Ulmi; Puji, Ari Andriyas; Haris, Aidil; Ahyaruddin, Muhammad; Asnawi, Mizan; Fitria, Sarah (LPPM UMRI, 2024)
Tangga Batu is one of the villages in Rokan Hilir Regency that receives many educational programs through outreach. This implementation focuses on several aspects, namely on the good practices of the intervention program and its impact which is carried and which targets starting from the general public, young women as prospective brides or not. Efforts to overcome this require multi-factor synergy and the role of stakeholders with the role of 1) central and regional governments as initiators, facilitators, and motivators 2) professional and academic organizations as think tanks, 3) development partners to strengthen initiation, collaboration, and monitoring and evaluation collaboration, 4) social institutions. This service aims to describe the intervention program that has been carried out to address local communities in maintaining reproductive health and gender equality. The intervention programs implemented by the central and regional governments, and motivators from academics and social partners have been running well, as indicated by the response of stakeholders who actively participate in the programs.